MARKET- BASED MANAGEMENT AND TAMALE POLYTECHNIC: A CRITICAL ANALYSIS OF THE ELEMENTS OF MARKET- BASED MANAGEMENT FRAMEWORK AND THE MANAGEMENT PHILOSOPHY AND SYSTEMS OF TAMALE POLYTECHNIC - Alhassan Baba Andani (International Journal of Research Science and Management, 2014)
Over the past few decades politicians and education experts have done all they can to help improve the performance of schools. An endless stream of management fads has been imported into education from the private sector in the hope that schools may learn to operate as excellent organizations working in free and competitive global markets (Stanfield, 2006). Most educational institutions operates under the command and control hierarchy system of management. Command and control management refers to the predominant system of management used by business organizations since the industrial revolution (Nobles and Redpath, 1995). Under this type of management, managers viewed their organization as “machines” and thought of employees as “cogs within the machine”.